Mengevaluasi Kepuasan Mahasiswa: Dampak Kualitas Pelayanan Pendidikan di Polteknik Harapan Bangsa Surakarta Jawa Tengah - Purbiyanto, Eko; Pamungkas, Tri (Indo-MathEdu Intellectuals Journal, 2024)
Independent assessment is a must for every educational institution, and one way is to conduct surveys to assess student satisfaction. The aim of this research is to analyze the level of student satisfaction with the learning process using the five dimensions of the SERVQUAL variable as independent variables and student satisfaction as the dependent variable. The total population was 185 respondents, the sample used the Disproportionate Stratified Random Sampling technique and used a questionnaire to obtain data. The results of this research process show that reliability has a significant effect on student satisfaction with a value of β = 0,163 with value r = 0,034. Responsiveness has a significant effect on student satisfaction with a value of β = 0,146 with value r = 0,045. Significant guarantee of satisfaction students with a value of β = 0,171 with value r = 0,041. Empathy is significant for student satisfaction with a value of β = 0,199 with value r = 0,007. Tangibles is significant for consumer satisfaction with a value of β = 0,274 with value r = 0,000. The F test of the SERVQUAL variable with customer satisfaction shows a significant simultaneous influence on the evidence with an F value of 31,191 > 0,05. And the contribution value of the influence of the five SERVQUAL variables on customer satisfaction with the adjusted R square result of 75,5%.